Information security management principles - Taylor, Andy (Information assurance expert); Alexander, David (Information security practitioner); Finch, Amanda (Computer scientist); Sutton, David (BCS, The Chartered Institute for IT, 2020)
This book is a pragmatic guide to information assurance for both business professionals and technical experts. The third edition has been updated to reflect changes in the IT security landscape and updates to the BCS Certification in Information Security Management Principles, which the book supports.